Aplikasi Regresi Data Panel Untuk Menganalisis Produktivitas Tenaga Kerja di Sulawesi Barat 2011-2023 - Hidayat, Ahmad Sovi; Yuniasih, Aisyah Fitri (Politeknik Statistika STIS, 2024)
Economic development encompasses all efforts to enhance the economy of a country, thereby improving the welfare of its society. Economic growth can occur through increased productivity in generating the output. During 2011-2023, Sulawesi Island experienced the highest increase in labor productivity compared to other islands. However, West Sulawesi Province faced an issue where its labor productivity ranked 30th out of 34 provinces in 2023. This condition has implications for the low-income and welfare levels of its society. This study aims to analyze the general overview of labor productivity and analyze the factors affecting labor productivity in West Sulawesi from 2011-2023 using panel data regression. The study results show that labor productivity has gradually increased since 2011 but has started to slow down since 2020. The panel data regression analysis indicates that gross fixed capital formation, investment credit, the proportion of high school and above workforce, and health expenditure positively affect labor productivity.